The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1093/molbev/msz153
|View full text |Cite|
|
Sign up to set email alerts
|

Epimutations in Developmental Genes Underlie the Onset of Domestication in Farmed European Sea Bass

Abstract: Domestication of wild animals induces a set of phenotypic characteristics collectively known as the domestication syndrome. However, how this syndrome emerges is still not clear. Recently, the neural crest cell deficit hypothesis proposed that it is generated by a mildly disrupted neural crest cell developmental program, but clear support is lacking due to the difficulties of distinguishing pure domestication effects from preexisting genetic differences between farmed and wild mammals and birds. Here, we use a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(105 citation statements)
references
References 95 publications
2
99
0
Order By: Relevance
“…A study of very recent domesticates of sea bass, which show no genetic differences from wild fish, found that these recent domesticates have epimutations (differences in patterns of DNA methylation) in various tissues, with about one fifth of the persistent epimutations being in genes that are expressed in embryonic structures, including the neural crest. Furthermore, the epimutated genes coincide with mutated genes in established domesticates (Anastasiadi and Piferrer, 2019). It is therefore plausible that a comparative study of epigenetic (e.g., methylation) differences among domesticates and humans will reveal many more substantial similarities and differences than gene-sequence differences, but at present there are only a few comparative studies that address this question.…”
Section: Similarities and Differences Between Humans And Domesticatesmentioning
confidence: 99%
“…A study of very recent domesticates of sea bass, which show no genetic differences from wild fish, found that these recent domesticates have epimutations (differences in patterns of DNA methylation) in various tissues, with about one fifth of the persistent epimutations being in genes that are expressed in embryonic structures, including the neural crest. Furthermore, the epimutated genes coincide with mutated genes in established domesticates (Anastasiadi and Piferrer, 2019). It is therefore plausible that a comparative study of epigenetic (e.g., methylation) differences among domesticates and humans will reveal many more substantial similarities and differences than gene-sequence differences, but at present there are only a few comparative studies that address this question.…”
Section: Similarities and Differences Between Humans And Domesticatesmentioning
confidence: 99%
“…Main observations might be summarized as follows: all studies considering brain tissue for which gene annotations were made available (n = 6) reported at least one match with DMC-related genes found in the present study. More speci cally, data of the single former sea bass epigenetic study performed at a genome-wide level [83] reported ve genes of the present study as differentially methylated in the brain (GLG1a, GFRA2, CELF2, PRKCQ, ROBO3), three in muscle (CILP1, FURIN, KBTBD13), one in testis (GLG1a), and any in liver (total: eight distinct genes). This indicated slightly more matches with the brain than with other organs investigated so far.…”
Section: Literature Surveysmentioning
confidence: 51%
“…Taking advantage of the epiGBS protocol that allow to process more samples [88], the number of individuals considered in this study is rather high (n = 70 distinct individuals), when most epigenomic studies in sh dealt with less than 30 individuals (range: n = 3 in [60]; n = 106 in [47] for a population study). In sea bass, Anastasiadi and Piferrer [83] previously reported a study that used 27 samples and as many libraries to be sequenced while our data were obtained from a unique library preparation. Our modi ed epiGBS protocol provides a considerable amount of information, certainly at a reasonable cost, to decipher methylation landscapes of sea bass or other species.…”
Section: Mining the Epigenome…mentioning
confidence: 99%
See 2 more Smart Citations